Asymmetric Information in Automobile Insurance: Evidence From Driving Behavior. Issue 4 (28th January 2019) - Geyer, Alois; Kremslehner, Daniela; Muermann, Alexander
Abstract: Based on a unique data set of driving behavior we test whether private information in driving characteristics has significant effects on contract choice and risk in automobile insurance. We define a driving factor based on overall distance driven, number of car rides, and speeding. Using local weather conditions, we account for the endogeneity of the driving factor. While this driving factor has an effect on risk, there is no significant evidence for selection effects in the level of third‐party liability and first‐party insurance coverage.